Lubiprostone: new treatment for chronic idiopathic constipation. Issue 4 (19th February 2014) - Chaplin, Steve; Ford, Alex
Abstract Lubiprostone (Amitiza) increases intestinal motility and is licensed for the treatment of chronic idiopathic constipation. In our New products review, Steve Chaplin presents the data relating to its efficacy and adverse events and Dr Alex Ford discusses its place in therapy.